Analisis Peran dan Fungsi Science Techno Park, Technology Transfer Office dan Technology Business Incubator untuk Mendukung Proses Komersialisasi Hasil Riset Perguruan Tinggi (Studi Kasus: Universitas Telkom) - Fitria, Sisca Eka; Fadila, Audri Chaira (Universitas Batanghari Jambi, 2024)
The government has launched a program to increase research in universities and commercialize research results in order to improve the economy and foster an entrepreneurial spirit from an early age, besides that it is expected to have an impact on society and the surrounding environment to support the era of globalization and digitalization which is increasingly developing today. the purpose of this study is to re-identify how the role and function of each of these entities in order to support the commercialization of research results of the Telkom University academic community and how the entities relate to each other which can be mapped through the Entity Relationship Diagram. this research uses qualitative research. The object of research is the technology transfer office, technology business incubator, and science techno park incorporated in the Bandung Techno Park area. The results of this study indicate that the function and role of STP is to create a culture of entrepreneurship and commercialize innovative products from the Telkom University academic community. the function and role of TTO is to protect Intellectual Property from the results of innovative products and commercialize in the form of Industrial Licensing or Cooperation contracts. The function and role of TBI is to develop entrepreneurship programs, business incubation and form spinoff companies. The relationship between these three entities is that STP oversees innovation products from upstream to downstream in its area, which is the Directorate of BTP and PPM. TTO helps the process of being born from the innovation products escorted by STP, which can be said to be BTP as a whole more specifically in the KI&TTO Center, then also PT BUT. TBI is in the middle of STP and TTO whether it needs to be incubated or can be directly commercialized, which is the BTP Incubator and Business Innovation (IIB) unit.